2014
DOI: 10.1016/j.jmb.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of Human SIRT1

Abstract: SIRT1 is a NAD+-dependent deacetylase that plays important roles in many cellular processes. SIRT1 activity is uniquely controlled by a C-terminal regulatory segment (CTR). Here we present crystal structures of the catalytic domain of human SIRT1 in complex with the CTR in an open apo form and a closed conformation in complex with a cofactor and a pseudo-substrate peptide. The catalytic domain adopts the canonical sirtuin fold. The CTR forms a β hairpin structure that complements the β sheet of the NAD+-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
142
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 66 publications
2
142
0
Order By: Relevance
“…The loop N, which connects the helix α3 of the zinc 2+ binding domain and the α2 helix of the Rossmann fold domain, is important for NAD + binding (Figure 2). By comparing crystal structures of SIRT5 with other sirtuins including SIRT1 (Davenport et al, 2014), SIRT2 (Moniot et al, 2013), SIRT3 (Jin et al, 2009), and SIRT6 , SIRT5 was observed to have a similar overall domain organization and fold to the structures of SIRT1, SIRT2, and SIRT3 ( Figure 3A), but a different domain fold with SIRT6 especially in zinc 2+ binding domain and catalytic site ( Figure 3B). As shown in Figure 3A, the catalytic sites of SIRT5, SIRT1, SIRT2, and SIRT3 superimpose very closely, and the residues around the catalytic site are relatively conserved.…”
Section: Structure Characteristics Of Sirt5mentioning
confidence: 98%
“…The loop N, which connects the helix α3 of the zinc 2+ binding domain and the α2 helix of the Rossmann fold domain, is important for NAD + binding (Figure 2). By comparing crystal structures of SIRT5 with other sirtuins including SIRT1 (Davenport et al, 2014), SIRT2 (Moniot et al, 2013), SIRT3 (Jin et al, 2009), and SIRT6 , SIRT5 was observed to have a similar overall domain organization and fold to the structures of SIRT1, SIRT2, and SIRT3 ( Figure 3A), but a different domain fold with SIRT6 especially in zinc 2+ binding domain and catalytic site ( Figure 3B). As shown in Figure 3A, the catalytic sites of SIRT5, SIRT1, SIRT2, and SIRT3 superimpose very closely, and the residues around the catalytic site are relatively conserved.…”
Section: Structure Characteristics Of Sirt5mentioning
confidence: 98%
“…Crystal structures of several archael, yeast, and human sirtuins have been solved, and they revealed a conserved catalytic core composed of a Rossmann-fold large lobe and a zinc-containing small lobe (Finnin et al 2001;Min et al 2001;Avalos et al 2002;Zhao et al 2003Zhao et al , 2013Schuetz et al 2007;Jin et al 2009;Pan et al 2011;Davenport et al 2014). NAD is bound in the cleft formed between the two lobes, with the nicotinamide group pointing inside of the cleft.…”
mentioning
confidence: 99%
“…The structure of the CD of SIRT1 with and without the C-terminal ESA polypeptide has been determined previously (Zhao et al 2013;Davenport et al 2014). The structure of the catalytic core resembles that of other sirtuins, and the ESA polypeptide folds into a β hairpin, which is juxtaposed with the parallel β strands of the Rossmann-fold domain and forms an extended, mixed β sheet (Davenport et al 2014).…”
mentioning
confidence: 99%
“…antibacterial, antiviral, anticancer, anti-inflammatory and properties [10], this collection represents a good starting point to search for novel inhibitors or modulators of sirtuins. Sirtuins share a highly conserved catalytic core composed of two subdomains; a large NAD + binding domain (Rossmann fold) and a smaller domain generated by two insertions in the NAD + binding domain, together with a helical module and a zinc-binding module [29,30].…”
Section: Introductionmentioning
confidence: 99%